Wearable teleoperation controller with 2-DoF robotic arm and haptic feedback for enhanced interaction in virtual reality - Zhang, Zheyuan; Qian, Chen (Frontiers in Neurorobotics, 2023)
In industries such as medicine and manufacturing, teleoperation is essential, with human operators interacting with remote robotic systems. A wearable device has been designed and manufactured to enhance sensitivity, wearability, and synchronization, enabling users to experience the sensation of grasping virtual objects. Force and shape rendering functions were tested across two prototypes. The effectiveness of the device was evaluated through user experiments. Participants were asked to rank the weights of three virtual balls and identify the direction of force applied to a virtual ball in separate tests.This wearable device incorporates a 2-DoF robotic arm, haptic sensors for finger gestures, and a Unity-powered virtual scene system. The accuracy of weight perception was tested by having participants rank three virtual balls with different masses. In another experiment, the direction of randomly applied forces to a virtual ball was identified by the participants. The results indicated that 73.3% of participants accurately ranked the balls by mass, and an overall correctness rate of 87.3% was achieved for force direction identification. A third experiment demonstrated the device's ability to render various shapes, with more accurate results for simple objects like spheres, while the rendering of more complex objects, such as cups and cones, presented challenges. These findings suggest potential applications for this device in haptic feedback and virtual reality contexts.